1967
DOI: 10.1002/pssb.19670240144
|View full text |Cite
|
Sign up to set email alerts
|

On the Mn‐Mn Interaction and the Structure of Optical Spectra of ZnS(Mn

Abstract: As is known for several years (1 to 4 ) the absorption and emission bands of ZnS type crystals activated by manganese show fine structure. The origin of this splitting is still controversial. McClure (2) explained the structure as zero-phonon lines due to transitions within both single Ban2+ ions and Mn2+ pairs split by the tetrahedral electric fields of the crystals. Brumage et al. for Mn-Mn pair transitions. The decay time of the luminescence being 6 function of the oscillator strength one should expect diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In general, Mn 2+ ions exhibit visible (VIS) PL originated from 4 T 1 excited state to 6 A 1 ground state, related to the relatively large energy gap (>17 000 cm −1 ) of the 3d 5 electronic configuration. [ 101 ] After the photoexcitation, the electrons in different excited states will return to the lowest excited state through nonradiative relaxation, and thus, the wavelength position of the emission bands relies on the crystal field surroundings of the host lattice, which allow the characteristics emission of Mn 2+ ions adjust from green to red. According to crystal field theory, if one Mn 2+ ion is surrounded by four ligands to form an independent MnX 4 2– tetrahedral unit, which is arranged in a specific form, the tetrahedrally coordinated Mn 2+ ions present a typical green emission with lower ligand field strength.…”
Section: Mn2+‐doped Luminescent Halide Perovskites With Different Strmentioning
confidence: 99%
“…In general, Mn 2+ ions exhibit visible (VIS) PL originated from 4 T 1 excited state to 6 A 1 ground state, related to the relatively large energy gap (>17 000 cm −1 ) of the 3d 5 electronic configuration. [ 101 ] After the photoexcitation, the electrons in different excited states will return to the lowest excited state through nonradiative relaxation, and thus, the wavelength position of the emission bands relies on the crystal field surroundings of the host lattice, which allow the characteristics emission of Mn 2+ ions adjust from green to red. According to crystal field theory, if one Mn 2+ ion is surrounded by four ligands to form an independent MnX 4 2– tetrahedral unit, which is arranged in a specific form, the tetrahedrally coordinated Mn 2+ ions present a typical green emission with lower ligand field strength.…”
Section: Mn2+‐doped Luminescent Halide Perovskites With Different Strmentioning
confidence: 99%
“…The luminescence of CaZnOS:Mn 2+ red phosphor shows a redshift and shortened decay lifetime against increasing Mn 2+ amount . Additionally, a decrease of PL intensity and red shifting are also reported in some other Mn 2+ -doped sulfides and selenides like ZnS:Mn 2+ , CdS:Mn, ZnSe:Mn, etc. Recently, the differences of Mn–Mn dipole–dipole interaction and spin-exchange interaction effects on modulating PL quenching of Mn 2+ emission have been discussed in a case of Mn 4 In 16 S 35 nanoclusters with well-controlled Mn–Mn distance . Introducing some heteronuclear ion, such as Cr 3+ , to magnetically couple Mn 2+ would be an option to shorten the Mn 2+ decay lifetime, but this inevitably introduces some unwanted emission peaks .…”
mentioning
confidence: 93%
“…Langer and Ibuki [l] have assumed that the phonon-assisted emission between Mn++ electronic levels in ZnS involves optical and acoustical modes of vibration of the pure host lattice. Gumlich et al [2] studying the relaxation time confirm this point of view. On the other hand, it has been shown that impurity-induced localized or resonant modes are the phonons involved in the assisted emission between the electronic levels [3 to 51.…”
Section: Introductionmentioning
confidence: 77%